Dengue Virus Activates Membrane TRAIL Relocalization and IFN-α Production by Human Plasmacytoid Dendritic Cells In Vitro and In Vivo - Gandini, Mariana (Public Library of Science, 2013)

(untitled)
BACKGROUND: Dengue displays a broad spectrum of clinical manifestations that may vary from asymptomatic to severe and even fatal features. Plasma leakage/hemorrhages can be caused by a cytokine storm induced by monocytes and dendritic cells during dengue virus (DENV) replication. Plasmacytoid dendritic cells (pDCs) are innate immune cells and in response to virus exposure secrete IFN-α and express membrane TRAIL (mTRAIL). We aimed to characterize pDC activation in dengue patients and their function under DENV-2 stimulation in vitro. METHODS & FINDINGS: Flow cytometry analysis (FCA) revealed that pDCs of mild dengue patients exhibit significantly higher frequencies of mTRAIL compared to severe cases or healthy controls. Plasma levels of IFN-α and soluble TRAIL are increased in mild compared to severe dengue patients, positively correlating with pDC activation. FCA experiments showed that in vitro exposure to DENV-2 induced mTRAIL expression on pDC. Furthermore, three dimension microscopy highlighted that TRAIL was relocalized from intracellular compartment to plasma membrane. Chloroquine treatment inhibited DENV-2-induced mTRAIL relocalization and IFN-α production by pDC. Endosomal viral degradation blockade by chloroquine allowed viral antigens detection inside pDCs. All those data are in favor of endocytosis pathway activation by DENV-2 in pDC. Coculture of pDC/DENV-2-infected monocytes revealed a dramatic decrease of antigen detection by FCA. This viral antigens reduction in monocytes was also observed after exogenous IFN-α treatment. Thus, pDC effect on viral load reduction was mainly dependent on IFN-α production CONCLUSIONS: This investigation characterizes, during DENV-2 infection, activation of pDCs in vivo and their antiviral role in vitro. Thus, we propose TRAIL-expressing pDCs may have an important role in the outcome of disease.